The Rainy Season : Three Lives in the New South Africa - Messitt, Maggie (Book collections on Project MUSE., 2015)
Just across the northern border of a former apartheid-era homeland sits a rural community in the midst of change, caught between a traditional past and a western future, a racially charged history and a pseudo-democratic present. The Rainy Season, a work of engaging literary journalism, introduces readers to the remote bushveld community of Rooiboklaagte and opens a window into the complicated reality of daily life in South Africa. The Rainy Season tells the stories of three generations in the Rainbow Nation one decade after its first democratic elections. This multi-threaded narrative follows Regina, a tapestry weaver in her sixties, standing at the crossroads where her Catholic faith and the AIDS pandemic crash; Thoko, a middle-aged sangoma (traditional healer) taking steps to turn her shebeen into a fully licensed tavern; and Dankie, a young man taking his matriculation exams, coming of age as one of Mandela's Children, the first academic class educated entirely under democratic governance. Home to Shangaan, Sotho, and Mozambican Tsonga families, Rooiboklaagte sits in a village where an outdoor butchery occupies an old petrol station and a funeral parlor sits in the attached garage. It's a place where an AIDS education center sits across the street from a West African doctor selling cures for the pandemic. It's where BMWs park outside of crumbling cement homes, and the availability of water changes with the day of the week. As the land shifts from dusty winter blond to lush summer green and back again, the duration of northeastern South Africa's rainy season, Regina, Thoko, and Dankie all face the challenges and possibilities of the new South Africa.